METABOLIC AND STRUCTURAL MYOCARDIAL DISEASE IN THE CONDITIONS OF EXPERIMENTAL ACUTE LUNG INJURY - O. O. Kostina; A. A. Hudyma; T. V. Datsko (Vіsnik Naukovih Doslіdžen', 2017)
The study of metabolic and structural myocardial disorders in conditions of experimental acute lung injury allows revealing the pathogenesis of processes and predicting the peculiarities of the course in this pathology.